A rare presentation of Mycoplasma pneumoniae with splenic nodules - Rodda, Alekhya; Reddy, Avinash; Dekate, Parag Shankarrao; Banothu, Kiran Kumar (Indian Journal of Case Reports, 2024)
Mycoplasma pneumoniae is a common respiratory pathogen that can cause a wide spectrum of extrapulmonary manifestations with neurological manifestations being the most common. Here, we report a rare case of splenic nodules in a 7-year-old girl with M. pneumoniae infection which responded well to macrolides. M. pneumoniae infection should be considered in children with extrapulmonary manifestations including splenic lesions.